Pedological Investigations of Pleistocene Glacial Drift Surfaces in the Central Yukon - Smith, C.; Tarnocai, C.; Hughes, O. (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 1986)
ABSTRACTDistinct soil morphologies associated with three different ages of Quaternary glacial deposits are characterized and subsequently named. Properties which provide a basis for distinguishing these in the field include solum depth, B horizon colour, clay skin development, coarse fragment weathering and periglacial features. A strong relationship is evident between the clay content at depth and the age of soil. Low values of Na pyrophosphate-extractable Fe and Al confirm the absence of any active podzol-forming processes even within the reddest (5YR, 2.5YR) soil horizons. Wounded Moose paleosols are the preserved soils observed on pre-Reid Glaciation (.2-1.2 Ma) deposits which show strong paleoargillic horizon development with red colours, high clay content, and common periglacial modification. Diversion Creek paleosols are the preserved soils found on Reid (80-120 ka) glacial deposits which show moderate paleoargillic horizon development and resemble the contemporary Gray Luvisols of the mid and southern boreal forest regions of Canada. Stewart soils are the weakly developed Brunisols formed on stable landform surfaces of McConnell (14-30 ka) glacial deposits. The Wounded Moose and Diversion Creek paleosols, while found commonly in local areas, occupy only a small proportion of the regional landscape.